2022
DOI: 10.3390/antiox11061100
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dietary Arthrospira platensis on Oxidative Stress Response and Pigmentation in Yellow Catfish Pelteobagrus fulvidraco

Abstract: In aquaculture, fish are often exposed to several stress conditions, which will cause oxidative disorder and bring about health and quality problems. Arthrospira platensis contains abundant bioactive ingredients, which are beneficial for animal health. This study was conducted to investigate the effects of A. platensis on pigmentation, antioxidant capacity, and stress response after air exposure of fish. A total of 120 yellow catfish Pelteobagrus fulvidraco (initial weight 70.19 ± 0.13 g) were divided into thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Carotenoid generally contributes to the yellowness or redness colour. However, some studies showed that carotenoid induces yellowness colour more than redness on the muscle of rainbow trout (Pulcini et al ., 2021) and yellow catfish (Liu et al ., 2022). Furthermore, phycocyanin pigment in S. platensis with the dark blue green colour might contribute to the increase in greenness more than blueness; hence, the b* ‐value did not show a negative value in all samples.…”
Section: Resultsmentioning
confidence: 99%
“…Carotenoid generally contributes to the yellowness or redness colour. However, some studies showed that carotenoid induces yellowness colour more than redness on the muscle of rainbow trout (Pulcini et al ., 2021) and yellow catfish (Liu et al ., 2022). Furthermore, phycocyanin pigment in S. platensis with the dark blue green colour might contribute to the increase in greenness more than blueness; hence, the b* ‐value did not show a negative value in all samples.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study on discus fish ( Symphysodon aequifasciatus ) found that carotenoids accumulated more in dorsal fin than in skin and muscle ( Song et al., 2017 ). A study in yellow catfish ( Pelteobagrus fulvidraco ) by Liu et al. (2022) also showed that carotenoids were more likely to be deposited in the skin than in the liver.…”
Section: Discussionmentioning
confidence: 98%
“…This could explain the total lack of response to a mixture containing both an attractive and repelling bacterium (Figure 4). Low (~1 mg/L) concentrations of CuSO 4 altered the bacterial community structure on the skin of adult Snook (Tarnecki et al., 2021) and the gills of Yellow catfish (Zhou et al., 2023). However, this effect likely differs between fish species.…”
Section: Discussionmentioning
confidence: 99%